Asal-Usul Alam Semesta dalam Perspektif Al-Qur’an dan Kosmologi Modern - Nikhlah Ziyadaturrohmah; Wita Wita; Azkia Ahada Ummu Sabilah; M. Naufal Hatsyafiq; Andi Rosa (Pusat Riset dan Inovasi Nasional, 2025)
The origin of the universe can be viewed from two main perspectives, the Qur'an and modern cosmology. In the Qur'an, the process of creation of the heavens and the earth is expressed through the terms al-khalq and al-bad', which indicate creation from existing matter or from nothing. Several verses such as QS. Al-Anbiya' [21]:30, QS. Fussilat [41]:11, and QS. Adz-Dzariyat [51]:47 describe the creation symbolically in line with scientific concepts such as the Big Bang theory and the expansion of the universe. This study uses a qualitative approach with a literature study method and philosophical reflection within the framework of Islamic educational philosophy. From the perspective of modern cosmology, the understanding of the beginning of the universe is based on the Big Bang theory, cosmic inflation, and microwave background radiation (CMB). This article also discusses the meeting point between revelation (naqlī) and empirical rationality ('aqlī), and emphasizes the importance of methodological dialogue between the science of interpretation and science. The findings of this study reveal that although the Qur'anic approach and scientific cosmology come from different bases, both can complement each other in deepening human understanding of the universe and its position as a living creature created by God. Therefore, the epistemological integration between the two becomes the basis for a more complete understanding in theological, scientific, and philosophical aspects of the origin of the universe